Level of risk management practice in Malaysia construction industry from a knowledge-based perspective - Omer, Manal Suliman; Adeleke, A. Q.; Lee, Chia Kuang (2019)
The construction industry is a competitive high-risk industry with unprecedented uncertainties in technology, budget and development processes. The need then evolved to develop a frame work for project performance in Malaysia construction company. This study investigated the associated problem in the management of risks in Malaysian construction projects using the knowledge-based approach. This perspective proposed a methodology based on a one-fold arrangement involving the application of risk management modelling function, evaluation of the comparative effectiveness and desired quality with the availability of a best practices model. The preliminary conclusion from these findings revealed that risk management in Malaysian construction projects is ineffective and still at a developmental stage. The applications of a knowledge-based framework, therefore, allow clients, contractors and consultants to develop a project’s risk management function based on best practices. The implementation of knowledge management will, therefore, avoid the organization the cost of repeating the same mistakes.This will invariably lead to improvement in the performance of construction work in Malaysia when incorporated as part of the organizational strategic plan.